The achievement and retention of Human Anatomy and Physiology terminology learning by adaptive of LINCS strategy: case study of Karen students, Maehongson College, Chiang Mai Rajabhat University - มหาทำนุโชค, ศิวาพร (Community and Social Development Journal, 2016)
The purpose of this experimental study were to investigate the achievement of Human Anatomy and Physiology terminology learning by adaptive of LINCS strategy : case study of Karen students, Maehongson College, Chiang Mai Rajabhat University. The sample group consisted of 18 students studying in Anatomy and Physiology 1-2 in the second semester of the academic year 2012 and the first semester of the academic year 2013, derived from simple random sampling by lottery method for Karen students. Use the equal in mean of the score of Anatomy and Physiology 1 to separate the control group and the experimental group. The experimental group was taught Anatomy and Physiology terminology by adaptive of LINCS strategy with they mother language. The tests in Anatomy and Physiology terminology learning were administered after teaching had finished and the second test done after the first test for 2 year later. Then the data were analyzed using percentage, mean and standard deviation. The result of the study was as : The Karen students taught through the use of adaptive of LINCS strategy with they first language had higher Anatomy and Physiology terminology ability and retention scores than control group.